Penguatan Literasi Menulis melalui Pendekatan Pembelajaran Mendalam - Anita Candra Dewi (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2026)
Writing literacy is a fundamental competency that plays a crucial role in developing critical and creative thinking skills in elementary school students. However, writing instruction in schools tends to be product-oriented and does not provide enough space for students' in-depth thinking processes. This study aims to comprehensively examine how a deep learning approach can strengthen elementary school students' writing literacy. The method used was a Systematic Literature Review (SLR) of national and international scientific articles published between 2022 and 2025. Data was obtained through Google Scholar, DOAJ, SINTA, and Garuda databases with keywords related to writing literacy and deep learning. Selected articles were analyzed using thematic analysis techniques. The study results revealed five main findings: (1) writing literacy serves as a foundation for critical and creative thinking, (2) deep learning increases engagement and meaning in learning to write, (3) contextual and multiliteracies strategies strengthen the quality of students' writing, (4) the teacher's role as a facilitator is crucial to the success of writing learning, and (5) deep learning has a positive impact on students' motivation and writing independence. These findings confirm that writing instruction oriented toward understanding, reflection, and real-life contexts can develop students' writing quality and analytical thinking. Thus, an immersive learning approach is a relevant pedagogical strategy for building a culture of meaningful writing literacy in elementary schools.